An analysis on the readiness of Bumiputera Small and Medium Industry (SMI) in Johor Bahru (JB) using E-Commerce as marketing tools - 621919 Abu Bakar Abdul Hamid; Hishamuddin Md. Som; Rohaizat Baharun (Skudai : Universiti Teknologi Malaysia, 2002)
36